2013
DOI: 10.1051/0004-6361/201321890
|View full text |Cite
|
Sign up to set email alerts
|

A diversity of dusty AGN tori

Abstract: Context. The AGN-heated dust distribution (the "torus") is increasingly recognized not only as the absorber required in unifying models, but as a tracer for the reservoir that feeds the nuclear super-massive black hole. Yet, even its most basic structural properties (such as its extent, geometry and elongation) are unknown for all but a few archetypal objects. Aims. In order to understand how the properties of AGN tori are related to feeding and obscuration, we need to resolve the matter distribution on parsec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
270
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(303 citation statements)
references
References 69 publications
25
270
4
1
Order By: Relevance
“…As discussed in e.g. Landt et al (2011), Burtscher et al (2013, Kishimoto et al (2013), andNetzer (2015), the T hot values calculated are close to the silicate dust grain sublimation temperature. This may suggest that the grains were formed in an oxygen-rich environment.…”
Section: Torus and Hostsupporting
confidence: 80%
“…As discussed in e.g. Landt et al (2011), Burtscher et al (2013, Kishimoto et al (2013), andNetzer (2015), the T hot values calculated are close to the silicate dust grain sublimation temperature. This may suggest that the grains were formed in an oxygen-rich environment.…”
Section: Torus and Hostsupporting
confidence: 80%
“…The most recent mid-infrared observations of nearby galaxies have revealed that there is a large scatter in the geometrical properties of their dusty tori (Burtscher et al 2013), and even very complicated structures of the dust within the central parsec were reported (Tristram et al 2014). …”
Section: Constraints On the Variable Absorber's Locationmentioning
confidence: 99%
“…This torus is optically thick, with a size of 0.1-10 pc (Suganuma et al 2006;Kishimoto et al 2007;Burtscher et al 2013). The region has a gas density in the range of 10 4 -10 7 cm −3 while the column density ranges from ∼10 22 to ∼10 25 cm −2 (Netzer 2013).…”
Section: Introductionmentioning
confidence: 97%